Impact of capital structure on corporate value: Review of literature - Sylwia Kruk (Journal of Risk and Financial Management, 2021)
The issue of capital structure in an enterprise is often described in the literature on the subject; however, theories are classified into various approaches, and their characteristics are often limited to selected theories. This work is an attempt at a synthetic presentation of the theory of capital structure. The aim of the article was to review and try to organise the most important theories of capital structure, paying attention to the influence of capital structure on the processes of creating value. The paper also highlights the most important theoretical works in this area. The study consists of two main parts. The first part indicates the diversity of defining the concepts of capital structure and indicates the approaches in classifying this structure. The second part characterises the theories of capital structure in the context of value creation. Based on the presented theories, it can be stated that there is no agreement as to whether and to what extent capital structure translates into the process of creating enterprise value. Therefore, it seems justified to conduct appropriate empirical research in this respect.
Keywords: 330; capital structure; capital structure decisions; capital structure theories; corporate value; external financing; finance management; financial management